Basis Normal Self-Dual dan Variannya - Irwansyah Irwansyah; Ahmad Muchlis; Intan Muchtadi Detiena (Institut Teknologi Bandung, 2012)
Basis normal self dual banyak digunakan dalam kriptografi. Dengan menggunakan basis tipe ini, dapat dikonstruksi aritmatika dengan kompleksitas rendah di lapangan hingga seperti perkalian dan perpangkatan. Tetapi, kelas basis ini hanya terdapat di lapangan hingga tertentu yaitu pada dengan q ganjil atau dengan q genap dan . Untuk mengatasi kekurangan ini, didefinisikan basis normal weakly self dual dan basis normal almost weakly self dual. Tulisan ini merupakan survei tentang hubungan antara basis normal self dual dan kedua variannya tersebut di lapangan hingga tertentu. Kata kunci: Lapangan hingga, Basis normal self dual, Basis normal weakly self dual, Basis normal almost weakly self dual. Self-Dual Normal Basis and Their Variants Abstract Self dual normal basis has many applications in cryptography. We can construct arithmatic devices with relatively small complexity in finite fields using this type of basis, such as multiplications and exponentials. Unfortunately, this type of basis exists in some particular finite fields only, i.e. in with q is odd or even and . To avoid this limitation, two variants of self dual normal basis are introduced, i.e. weakly self dual normal basis and almost weakly self dual normal basis. In this paper, we survey connections among three type of normal basis above in particular finite fields. Keywords : Finite fields, Self dual normal basis, Weakly self dual normal basis, Almost weakly self dual normal basis.